Intermediate Temperature Internal Oxidation of a SiC/SiCN Composite with a Polymer‐Derived Matrix1. Issue 9 (26th May 2016) - Poerschke, David L.; Rossol, Michael N.; Zok, Frank W.
Abstract : SiC‐based composites exhibit oxidative embrittlement at intermediate temperatures. Although the mechanisms of internal oxidation in composites with initially hermetic matrices have been studied extensively, comparable studies on composites with semipermeable matrices, such as those produced by polymer infiltration and pyrolysis, have not been reported. The present article focuses on the latter class of composites, specifically a SiC f /SiCNm with a dual BN/Si3 N4 fiber coating. It describes detailed SEM and TEM analyses of the microstructure before and after oxidation in dry air or water vapor at 800°C. The results show that internal oxidation is more aggressive in water vapor and occurs appreciably even in the absence of an applied stress. The sequence of oxidation of the constituent phases appears to be consistent with the underlying thermodynamic hierarchy for the respective oxidation reactions. Notably, contrary to existing models based on preferential oxidation of BN coatings, oxidation occurs first on the SiC fiber surfaces and the Si3 N4 overcoat; crystalline BN remains even after significant fiber and matrix oxidation has occurred. The results are discussed in terms of rate‐controlling kinetic processes, the effect of oxidant type, and applied stress.